Optical absorption and stability enhancement in mixed lead, tin, and germanium hybrid halide perovskites for photovoltaic applications. (July 2022) - Taya, Ankur; Kumar, Sarvesh; Hackett, Timothy A.; Kashyap, Manish K.
Abstract: Hybrid halide perovskite (HHP) materials present flexible version of next-generation solar cells and among these, Methyl ammonia lead iodide, i.e., CH3 NH3 PbI3 (MAPbI3 ), dominated the research field owing to its excellent photovoltaic properties, but its commercial deployment was halted due to the presence of toxic Pb. Mixed cation and anion strategies can play a significant role in improving structural stability and reducing toxicity. Partial or full replacement of Pb with congener but non-toxic elements such as Sn and Ge can facilitate the large uptake of HHP solar cells. In this work by first-principles calculations, we explore the potential alternatives to MAPbI3 by investigating the structural, electronic and optical properties of MAPb1-x-y Snx Gey I3 [(x, y) = (0, 0.5), (0.25, 0.25) (0.5, 0)]. The present report indicates that via Ge and Sn-doping in MAPbI3, the bandgap can be tuned from 1.16 eV to 0.77 eV. Meanwhile, in the Sn/Ge/Sn–Ge doped MAPbI3, the optical absorption coefficients get enhanced in the visible region and in the regions as far as mid-infrared, making them better alternatives to toxic MAPbI3 for photovoltaic applications. Moreover, owing to the outstanding photovoltaic characteristics, MAPb0.50 Sn0.25 Ge0.25 I3 is proposed as an absorber layer material for the efficient perovskite solar cell modules. Highlights: A range of Ge and Sn doping concentration in MAPbI3 is explored to tune the bandgap from 1.16 eV to 0.77 eV. In Sn/Ge/Sn–Ge doped MAPbI3, the optical absorption gets enhanced not only in the visible region but also in mid-infrared. MAPb0.50 Sn0.25 Ge0.25 I3 is proposed as an alternate absorber layer in place of pure MAPbI3 for HHP based solar cells.